Experiences with a Commercial ECDIS - Lanziner, H.; Michelson, D.; Lachance, S.; Williams, D. (The International Hydrographic Review, 2015)
The integration of accurate positioning and electronic charts provides an extremely valuable tool to the mariner when navigating under hazardous conditions. This paper describes the experiences of two organizations in Canada who work under such conditions. On the St. Lawrence River, the Canadian Coast Guard is using the PINS 9000, a commercial ECDIS, for ice breaking chores with few, if any, other aids and has demonstrated operational savings. Marine Atlantic, Inc., uses the same system for ferry navigation into and out of Port aux Basques, Newfoundland, where it not only assists in meeting a tight schedule, but also enhances safety when operating in difficult conditions.